PENGARUH TAX AVOIDANCE TERHADAP SALARY DISTRIBUTION - Clara Yully Diana Ekaristi; Apip Apip (EKUITAS (Jurnal Ekonomi dan Keuangan), 2023)
The study examines the impact of tax avoidance on salary distribution in the Indonesian property and real estate sectors. The study uses purposive sampling techniques by taking a sample of 65 companies on the Indonesian Stock Exchange from 2019–2020. This hypothesis is tested through the application of the double linear regression method. This research shows that tax evasion has no statistically significant influence on wage distribution. The size and age of the company, as well as its modalities, have a statistically significant and positive influence on wage distribution. On the contrary, audit committees and return on equity (ROE) have a statistically significant negative influence on wage distribution. The importance of capital's role in unemployment income has been proven significantly and provides substantial benefits. The variables return on asset (ROA), liquidity, leverage, growth, and accumulated wages show positive influences on wage distribution but are not statistically significant. These findings show that there is no statistically significant influence of increases in the debt-to-equity ratio (DER), cash effective tax rate (CETR), effective tax rate (ETR), and average wage on salary distribution.